The Sentinel Islanders : The Most Isolated Tribe in the World - Sasikumar, M. (Brill | Manohar Publishers & Distributors, 2023)
The Sentinel Islanders, also called the Sentinelese, are one of the five Particularly Vulnerable Tribal Groups (PVTGs) of the Andaman and Nicobar islands. They live in the North Sentinel Island of the Andaman group of Islands situated in the Bay of Bengal. They are, perhaps, the only truly isolated hunter-gatherer tribal community in the world today. Of the five PVTGs, the Sentinel Islanders are usually described as the 'most uncontacted' and 'most reclusive' people on earth. Till today, this group has maintained their independent existence, repelling all attempts to directly engage with and contact them. They remained steadfast in opposition to all the efforts of the colonial and post-colonial administration to contain them with the might of their bows and arrows. Incredibly, they also managed to survive the 2004 Indian Ocean Tsunami, which had a devastating effect on the people of the lsland groups. Curiosity about their lifestyles has endured all these years in all sections of society since 1771, when an East India Company vessel sailing past their island spotted the presence of lights there. It was, however, in November-December 2018, that the Sentinelese received international attention, when an American national went missing after having ventured to encroach upon their land. It was alleged that a Sentinelese killed him after warning him twice to leave the island. This has further reinforced the image of ferocity of a people who do not want any interference from the outside world in their subsistence patterns and long to remain as the 'masters of their island'. In this book, an attempt has been made to understand their way of life from an anthropological perspective in the light of available historical and anthropological evidences.